2007
DOI: 10.1158/0008-5472.can-07-0516
|View full text |Cite
|
Sign up to set email alerts
|

Clusterin Isoforms Differentially Affect Growth and Motility of Prostate Cells: Possible Implications in Prostate Tumorigenesis

Abstract: Besides a fully processed, secreted form of clusterin (sCLU), an alternative proapoptotic form of the protein targeting the nucleus (nCLU) was recently described. The possible differential roles played by the two clusterin forms in growth and motility of nonmalignant and malignant prostate cells are investigated here. sCLU or nCLU was transiently transfected in both androgen-independent prostate cancer cells (PC3 and DU 145) and immortalized prostate epithelial cells (PNT1A, a nontumoral control). Then, cell g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
45
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 51 publications
10
45
0
Order By: Relevance
“…Accordingly, we document that nCLU production by MDA-7/IL-24 caused G 2 /M phase arrest followed by apoptosis. Furthermore, it has been reported that nCLU has potent anti-migratory activity through its binding to α-actinin (Moretti et al, 2007) and our present results revealed that nCLU generated by MDA-7/IL-24 is involved in altering cytoskeleton and resulted in decreased cell migration. Moreover, MDA-7/IL-24 decreased cell proliferation and colony formation with apoptosis induction in sCLU-overexpressing prostate cancer cells.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Accordingly, we document that nCLU production by MDA-7/IL-24 caused G 2 /M phase arrest followed by apoptosis. Furthermore, it has been reported that nCLU has potent anti-migratory activity through its binding to α-actinin (Moretti et al, 2007) and our present results revealed that nCLU generated by MDA-7/IL-24 is involved in altering cytoskeleton and resulted in decreased cell migration. Moreover, MDA-7/IL-24 decreased cell proliferation and colony formation with apoptosis induction in sCLU-overexpressing prostate cancer cells.…”
Section: Discussionsupporting
confidence: 71%
“…Overexpression of nCLU has been reported to induce G 2 /M phase arrest and caspase-dependent apoptosis in prostate cancer cells . Similarly, previous studies showed that transfection with "full-length" CLU cDNA produced both sCLU and nCLU in nonmalignant PNT1A cells, whereas only sCLU was found in cancer cells (Moretti et al, 2007). This escape mechanism limiting production of the proapoptotic nCLU from the full-length CLU gene might play a crucial role in prostate tumorigenesis.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…It consists of 2 isoforms: secretory clusterin (sCLU) and intracellular clusterin (nCLU). The former has been described as a long-length CLU (also known as sCLU), while the latter as a nuclear form, truncated CLU (also known as nCLU) (9,10). sCLU is known as an extracellular secreted glycoprotein in the mature form that is upregulated in a variety of cell lines in response to stress and enhances cell survival (11).…”
Section: Introductionmentioning
confidence: 99%
“…The progressive decrease of CLU expression is clearly one of the molecular changes implicated in the progression from pure BAC to invasive adenocarcinoma, and confirm the possible role of CLU as a tumor suppressor factor against infiltration or invasiveness. In fact, CLU has been already found as an important regulator of cell fate, negatively controlling further progression and invasiveness [12,32].…”
Section: Discussionmentioning
confidence: 99%